A contrastive study of the speech act of refusal among EFL speakers / Zhao Chunli - Zhao, Chunli (2016)
Refusal, as one of the most frequently performed speech acts in our daily lives, has recently gained increasing attention in pragmatics. In academic settings in Malaysia, for example, the opportunity for interaction frequently occurs among students from different cultural backgrounds. The purpose of this study is thus to investigate two groups of EFL speakers, namely Chinese and Iraqis, in their realization of the speech act of refusal in an academic setting. In order to achieve the purpose of this study, the study seeks to explore the similarities and differences of refusal strategies employed by Chinese (mainland China) and Iraqi EFL speakers in making refusals. The participants of this study consist of 30 postgraduates (15 Chinese and 15 Iraqi Arabs) who are studying in University of Malaya. The role-play scenario used to collect data consists of eight different situations which have been designed to elicit responses of refusals from the participants in four different initiating speech acts such as: suggestions, requests, invitations, and offers. Each situation involves two social variables: social power and social distance. The data were analyzed based on classification of refusals from Beebe et al (1990). The results show that Chinese and Iraqi EFL speakers have different preferences in the choice of refusal strategies. The findings also reveal that there are some similarities and difference between Chinese and Iraqis in terms of frequency of semantic formula, order of semantic formula, content of semantic formula.